Evaluation of high altitude training camps with heart rate recovery and heart rate variability analysis: beneficial effect in elite swimmers - Torun, A.; Kilic, S.; Uzun, M.; Simsek, U.; Aslan, G.Y.; Kahraman, G. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND The available evidence on the impact of altitude training on sports performance is inconclusive. Heart rate variability (HRV) and heart rate recovery (HRR) are among the most frequently used parameters in athletic performance analysis and monitoring. Our study aims to investigate the effect of high altitude training on HRR and HRV, which are reliable predictors of athletic performance.